Superstitions and Civilian Displacement : Evidence from the Colombian Conflict - Kaplan, Oliver (World Bank, Washington, DC, 2022)
Violence during armed conflict has been explained using a variety of theories, including rationality, organizational dynamics, and personal and collective grievances. These explanations overlook the significance of so-called “irrational” belief systems that are found in different countries among both combatants and the general population. Conflict-related religious and superstitious beliefs can shape civilians’ faith, resolve, optimism, social ties, and therefore levels of risk-acceptance and decisions to displace from their communities. This study explores new survey and interview data from Colombia from 2016–2019 and shows that a substantial share of the conflict-affected population holds a variety of conflict-related superstitious beliefs. The determinants of these beliefs are analyzed and impacts assessed on three key displacement-related outcomes: How likely are individuals to displace if their town is attacked; how they cope with the difficulties of daily life in conflict zones (resilience); and would they recommend that displaced relatives return home. Regression analysis, statistical matching techniques, and interview and focus group accounts indicate how superstitions and religious beliefs and practices affect these outcomes. The paper concludes with implications for the field of conflict studies, as existing theories of conflict and violence may be based on incomplete foundations and inaccurate models of decision-making.